Conceptualizing Ethical Issues of Humanitarian Work: Results From a Critical Literature Review - Côté, Louis; Drolet, Marie-Josée (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2021)
This article presents results of a critical review of the literature discussing the ethical issues arising in humanitarian work, following the method proposed by McCullough, Coverdale and Chervenak. Our aim was primarily to focus on how the ethical issues arising in humanitarian work are conceptualized within the literature we reviewed. We think that properly conceptualizing the ethical issues which humanitarian workers may face can provide avenues to better respond to them. We analysed 61 documents, as part of a literature review, which revealed that there truly is a need, amongst the authors and in humanitarian work, to discuss ethics. Indeed, even if only a small number of authors define explicitly the words they use to discuss ethics, the great quantity that we have uncovered in the documents seem to suggest vast and rich grounds upon which to address ethical issues. We believe it to be important that the ethical issues of humanitarian work are increasingly addressed in the literature and argue that it would be helpful for the vocabulary used by authors to be employed and developed even more rigorously, so that their discussions show more precision, coherence, relevance, exhaustiveness, and sufficiency. The review of the literature, as well as the resulting analysis in this article, is part of a broader project to suggest a way to conceptualize the ethical issues of humanitarian work based on the strengths and innovations of this and other studies.